2014
DOI: 10.1212/wnl.0000000000000526
|View full text |Cite
|
Sign up to set email alerts
|

Effects of APOE ε4, age, and HIV on glial metabolites and cognitive deficits

Abstract: Objective: We aimed to evaluate the combined effects of HIV and APOE e4 allele(s) on glial metabolite levels, and on known cognitive deficits associated with either condition, across the ages. Results: Frontal white matter myo-inositol was elevated in subjects with HIV across the age span but showed age-dependent increase in seronegative subjects, especially in APOE e41 carriers. In contrast, only seronegative APOE e41 subjects showed elevated myo-inositol in parietal cortex. All APOE e41 subjects had lower to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 38 publications
3
55
0
Order By: Relevance
“…Neuroimaging studies provide evidence of accelerated aging processes in HIV+ adults (Chang et al, 2014; Holt, Kraft-Terry, & Chang, 2012; Thomas, Brier, Snyder, Vaida, & Ances, 2013), with some indication that aging may increase HIV-related neural change (Clark & Cohen, 2010; Cysique et al, 2013). In addition, studies of facial emotion recognition in non-HIV samples indicate that older adults are less accurate at recognizing fearful expressions than younger adults (Calder et al, 2003; Circelli, Clark, & Cronin-Golomb, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Neuroimaging studies provide evidence of accelerated aging processes in HIV+ adults (Chang et al, 2014; Holt, Kraft-Terry, & Chang, 2012; Thomas, Brier, Snyder, Vaida, & Ances, 2013), with some indication that aging may increase HIV-related neural change (Clark & Cohen, 2010; Cysique et al, 2013). In addition, studies of facial emotion recognition in non-HIV samples indicate that older adults are less accurate at recognizing fearful expressions than younger adults (Calder et al, 2003; Circelli, Clark, & Cronin-Golomb, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Although neurons exhibit activity-dependent uptake of myo-Inositol (Uldry et al, 2004), myo-Inositol is more concentrated in glial cells than neurons (Brand et al, 1993;Griffin et al, 2002), and may be critical for glial osmoregulatory functioning (Strange, 1992;Fisher et al, 2002). In neuro-inflammatory conditions, elevated myo-Inositol levels are presumed to reflect astrocyte and microglial activation (Chang et al, 2014, Kirov et al, 2013; conversely, reduced myo-Inositol levels have been interpreted as evidence of astrocyte necrosis in neuromyelitis optica (Ciccarelli et al, 2013). Several postmortem studies have found reduced density of glial cells (Ongür et al, 1998;Hamidi et al, 2004) and decreased concentration of protein markers specific to astrocytes in MDD (MiguelHidalgo et al, 2000;Miguel-Hidalgo et al, 2011;MiguelHidalgo et al, 2014), providing a histological basis for interpreting reduced myo-Inositol levels in MDD as evidence of glial dysfunction (Coupland et al, 2005;Chen et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…One is ART-induced neurotoxicity, which is now known to result in part by dysregulated A[H9252]PP processing and subsequent deposition of Aβ plaques in the brain. Based on neuropathological data [11, 205], genetic screening [206, 207], and CSF markers [208], researchers have raised the possibility that AD may be becoming more common in HIV patients on cART. Although the exact mechanisms through which cART contributes to Aβ deposition in the brain are unknown, neurotoxic effects of ART drugs such as mitochondrial dysfunction [81, 91, 209], increased oxidative and ER stress [82, 92, 93, 210, 211], and neuronal damage and synaptic loss [212, 213] are now linked to altered AβPP processing and Aβ deposition in the brains of HIV patients.…”
Section: Contribution Of Hiv Viral Proteins and Cart To The Developmementioning
confidence: 99%